Digital transformation and customer satisfaction in the retail industry in emerging countries: Case study in Hanoi, Vietnam - Phuong, Nguyen Van; Dung, Tran Viet; Loc, Nguyen Van; Thanh, Tran Thi Mai; Duong, Nguyen Thi Thuy; Trang, Do Thi My; Cuc, Ly Thu (Edelweiss Applied Science and Technology, 2024)
This study aims to investigate the impact of digital transformation on customer satisfaction in the retail industry, focusing on the mediating roles of perceived value and technology acceptance in emerging countries - research in Hanoi, Vietnam. Based on existing literature, we proposed a conceptual model that posits digital transformation as a key driver of customer satisfaction, both directly and indirectly, through its influence on perceived value and technology acceptance. The data was collected from 362 retail customers in Hanoi, Vietnam. The collected data was analysed using PLS-SEM by SmartPLS software version 4.1. The results of this study show the significant positive impact of digital transformation on customer satisfaction in the retail industry. Retailers should pay attention to applying digital technologies to enhance customer experience, create added value, and foster stronger engagement. Furthermore, the study reveals that perceived value and technology acceptance mediate this relationship. From that, retailers should prioritize enhancing customer perceptions of value and facilitating the acceptance of digital technologies. The findings of this study contribute to the understanding of knowledge on digital transformation in retail by providing empirical evidence for the mediating roles of perceived value and technology acceptance in shaping customer satisfaction. In addition, the findings offer valuable insights for retail managers seeking to leverage digital technologies to enhance customer experiences and drive business success.